2015
DOI: 10.1007/s10661-015-4711-3
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air quality and the effects of air pollutants on otolaryngology in Beijing

Abstract: To investigate temporal patterns, pollution concentrations and the health effects of air pollutants in Beijing we carried out time-series analyses on daily concentrations of ambient air pollutants and daily numbers of outpatient visits for otolaryngology over 2 years (2011)(2012) to identify possible health effects of air pollutants. The results showed that PM 10 was the major air pollutant in Beijing and that air quality was slightly better in 2012 than in 2011. Seasonal differences were apparent for SO 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…One study conducted in Beijing found that the levels of PM 10 , NO 2 , and SO 2 were positively associated with the number of outpatient visits to otolaryngology departments during winter [6]. Although the study settings are different, and although we found no associations between NO 2 and SO 2 levels and disease, it is notable that PM 10 levels were closely associated with ENT disease in two Asian studies.…”
Section: Discussioncontrasting
confidence: 62%
“…One study conducted in Beijing found that the levels of PM 10 , NO 2 , and SO 2 were positively associated with the number of outpatient visits to otolaryngology departments during winter [6]. Although the study settings are different, and although we found no associations between NO 2 and SO 2 levels and disease, it is notable that PM 10 levels were closely associated with ENT disease in two Asian studies.…”
Section: Discussioncontrasting
confidence: 62%
“…36,37 Exposure to a combination of pollutants accelerates the onset of allergic rhinitis, particularly by inducing exacerbations. 33 These findings are consistent with conclusions made in numerous other studies. 3638…”
Section: Air Pollution In Low- and Middle-income Countriessupporting
confidence: 92%
“…A study in Beijing evaluated the influence of air pollution on otolaryngology out-patient attendance. 33 Nitrogen dioxide and sulphur dioxide concentrations showed positive associations with out-patient attendance. 33 Exposure to air pollution early in life increases the risk of both upper and lower respiratory tract infections in children, including middle-ear infection.…”
Section: Air Pollution In Low- and Middle-income Countriesmentioning
confidence: 93%
See 2 more Smart Citations